Analisis Kinerja Pegawai guna Menunjang Kinerja Organisasi dalam Memberikan Pelayanan Masyarakat - Siti Noor Hidayati; Syamyudi Syamyudi (Universitas Proklamasi 45 Yogyakarta, 2017)
Employee of UPTD PKB Dinas Perhubkominfo Kabupaten Sleman in providing services of motor vehicle testing must meet the criteria as contained in the SK MENPAN No.63/2003 covering six criterias that are service procedure, service time, service cost, service product, infrastructure, and competence of service provider. Consumer satisfaction of the application of motor vehicles testing measured with five characteristics, that are tangibles, reliability, responsiveness, assurance, and empathy. The results of this research indicate that performance of employee in service will support organizational performance significanly (Z-test). The variables of organizational performance (service procedure, service time, service cost, service product, infrastructure, and competence of service provider) have an effect to increase consumer satisfaction of the application of motor vehicles test, partially (t-test) and also simultaneously (F-test). In this research, the dominant effect of customer satisfaction to organizational performance is infrastructure.